Motivating Factors Influencing Online Learning Among University Students: A Study of a Private University in Malaysia - Kadiresan, Vimala; Sujin, Jung; Rahim, Hazrita Ab; Rasu, Farrell (Journal of Social Science Studies, 2021)
The purpose of this study is to examine the motivating factors that influence online learning among university students during the Covid-19 pandemic era. Due to sudden transformation from traditional face-to-face learning approach to remotely digital learning, some present studies revealed that students’ motivation in online learning is probably the most important factor that educators can target to improve learning. There are four chosen independent variables in this study which are student’s participation, role of instructors, online learning environment and technical infrastructure affect online learning. This research uses a survey method where 150 questionnaires are distributed online. Then, the collected data are tabulated to analyze the findings and results.